2017
DOI: 10.3390/toxins9050172
|View full text |Cite
|
Sign up to set email alerts
|

Doses of Immunogen Contribute to Specificity Spectrums of Antibodies against Aflatoxin

Abstract: Research about antibody specificity spectra was conducted to develop single-specific antibodies or broad-specific antibodies. Aflatoxins, as one class of high-toxicity mycotoxins, were selected as the research targets to investigate the effect of the immunogen dose on antibody specificity spectra. For this aim, 16 monoclonal antibodies were induced by low or high doses of aflatoxin B1-BSA, and 34 monoclonal antibodies were induced by low or high doses of aflatoxin M1-BSA. The specificities of the antibodies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Taking aflatoxin B1 as the research object, the effect of immunogen dose on antibody specificity and class broad specificity was discussed. e results showed that low-dose immunogen can improve the specificity of the antibody, and high-dose immunogen can increase the broad specificity of the antibody, and the research results provided reference for the development of new antibodies [54]. However, whether the results of this study are applicable to the preparation of antibodies to ZEN and other small molecule compounds remains to be further explored in the future.…”
Section: Synthesis Methods Of Zen Immunogen and Characteristicsmentioning
confidence: 78%
“…Taking aflatoxin B1 as the research object, the effect of immunogen dose on antibody specificity and class broad specificity was discussed. e results showed that low-dose immunogen can improve the specificity of the antibody, and high-dose immunogen can increase the broad specificity of the antibody, and the research results provided reference for the development of new antibodies [54]. However, whether the results of this study are applicable to the preparation of antibodies to ZEN and other small molecule compounds remains to be further explored in the future.…”
Section: Synthesis Methods Of Zen Immunogen and Characteristicsmentioning
confidence: 78%
“…Five six-week-old female Balb/c mice were immunized using a high ZEN-BSA conjugate dose at long intervals with multiple-site subcutaneous injections [22,43]. For the first immunization, each mouse was subcutaneously injected on four sites (on the back) with 200 µg of the ZEN-BSA conjugate dissolved in sterilized PBS and emulsified with an equal volume of FCA.…”
Section: Zen Mab Preparation 461 Animal Immunizationmentioning
confidence: 99%
“…The influencing factors of the immunization method include the injection route, dosage, interval, adjuvant usage, frequency, and individual animal differences, with the dosage and the interval being the key factors. Some scholars have shown that a low immunogen dose induces a narrowspectrum specificity of antibodies, while a high dose has a broad-spectrum of specificity of antibodies [43]. An immunogen elicits the generation of memory B cells, which require certain immunization intervals to clone and proliferate, producing several specific antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The CR values of the 8H10 mAb for AFB1, AFB2, AFG1, and AFG2 were 100%, 60.47%, 65.97%, and 14.83%, respectively. Li et al [ 38 ] reported that the dose of immunogen had a great contribution to the specificity and broad spectrum of AFs mAb, and the low dose of immunogen helped to obtain a specific narrow-spectrum mAb. The high dose of immunogen helped to obtain a specific broad-spectrum mAb.…”
Section: Preparation Of a Single Universal Antibody For Taf Immunomentioning
confidence: 99%